4x 3 2 4 x 2 2x 1
![4x 3 2 4 x 2 2x 1](https://media.cheggcdn.com/study/1c2/1c2e61ed-444f-4ca6-94ec-4c7cfd6d5746/image.png)
- 4x 3 x 2 2x 1 ) = 4 3x
- 2 3 4 x 2 )= 5 2x 1 2 7 4x
- 6 x 2 4 )- 4x x 3 )= 2x 2 12x 12
- 4x 1 2 2x 3 6x 5 4 x 2 2 16x
- X 4 2x 3 3x 2 4x 6 )/( x 2 2x 1
- 3 2x 1 )- 4 2 x )= 4x 5 2x 2
- 4x 1 2 4 2x 3 2 x 4 0
- X 2 )( x 4 2x 3 4x 2 8x 16
- 9 4x 3 2 4 x 2 2x 1
- 3x 4 4x 3 6x 2 x 4 )/( 3x 2 2x 1
- 4x 4 2x 3 x 2 5x 8 )/( x 2 2x 1
- 8x 4 18x 3 9x 2 4x 2 )/( x 2 2x 1
- (- 4x 2 x 12 )+( 2x 3 3x 2 4
- 4x 4 2x 3 x 2 5x 8 divided by x 2 2x 1